Zakat Sebagai Automatic Stabilizer Dalam Ekonomi Makro - Muthmainnah Muthmainnah; Saadal Jannah; St. Sarifah Najwa; Fauziyah Fzh; Mutia Munthar; Andini Ardianti; Shabrina Al Haya`; Rifka Annisa; Syarifah Salma (JES (Jurnal Ekonomi Syariah), 2026)
This study aims to analyze the role of zakat as an automatic stabilizer in Islamic macroeconomics, particularly in the mechanisms of economic stabilization, inflation control, and its implementation within modern economic systems. The research employs a qualitative method with a descriptive-analytical approach through library research, utilizing secondary data from books, scientific journals, and relevant official documents. The results of the study indicate that zakat has a mechanism aligned with the concept of an automatic stabilizer, in which zakat collection increases along with the rise in people's income, while its distribution to eligible recipients (mustahik) continues during economic downturns, thereby maintaining purchasing power and public consumption. In addition, zakat plays a role in controlling inflation through a more equitable redistribution of income and the prevention of wealth concentration. The implementation of zakat in the modern economy also demonstrates significant potential in supporting economic stability, particularly through the role of zakat management institutions, although it still faces various challenges related to public awareness and institutional management. Therefore, zakat can function as a macroeconomic instrument that is oriented not only toward stability but also toward social justice.